Active breaks: a strategy to counteract sedentary behaviors for Health Promoting Schools. A discussion on their implementation in Italy - Dallolio, L.; Gallè, F.; Masini, A.; Valeriani, F.; Ceciliani, A.; Di Cagno, A.; Galeone, D.; Pecoraro, P.; Valerio, G.; Liguori, G.; Romano Spica, V.; Brandi, G.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
School Active Breaks are short bouts of physical activity (5-15 minutes) conducted by appropriately trained teachers and delivered during or between curricular lessons. They are a good strategy to counteract sedentary behaviors, and a growing body of evidence shows that they can represent also a tool to promote and improve health, school wellbeing and academic achievements. On 19 February 2022, the Working Group on Movement Sciences for Health of the Italian Society of Hygiene, Preventive Medicine and Public Health organized an Awareness Day on the effectiveness, usefulness and feasibility of School Active Breaks, opened to teachers, educators, school leaders, pediatricians, personnel from Departments of Prevention and Public Health and Health Policy-makers.During the event, the testimonies about the experiences already carried out in Italy showed that School Active Breaks are an effective intervention that each school can easily include in its educational offer and apply in any context.